Biochemical and Phenotypic Abnormalities in Kynurenine Aminotransferase II-Deficient Mice - Yu, Ping (American Society for Microbiology, 2004)
Kynurenic acid (KYNA) can act as an endogenous modulator of excitatory neurotransmission and has been implicated in the pathogenesis of several neurological and psychiatric diseases. To evaluate its role in the brain, we disrupted the murine gene for kynurenine aminotransferase II (KAT II), the principal enzyme responsible for the synthesis of KYNA in the rat brain. mKat-2(−/−) mice showed no detectable KAT II mRNA or protein. Total brain KAT activity and KYNA levels were reduced during the first month but returned to normal levels thereafter. In contrast, liver KAT activity and KYNA levels in mKat-2(−/−) mice were decreased by >90% throughout life, though no hepatic abnormalities were observed histologically. KYNA-associated metabolites kynurenine, 3-hydroxykynurenine, and quinolinic acid were unchanged in the brain and liver of knockout mice. mKat-2(−/−) mice began to manifest hyperactivity and abnormal motor coordination at 2 weeks of age but were indistinguishable from wild type after 1 month of age. Golgi staining of cortical and striatal neurons revealed enlarged dendritic spines and a significant increase in spine density in 3-week-old mKat-2(−/−) mice but not in 2-month-old animals. Our results show that gene targeting of mKat-2 in mice leads to early and transitory decreases in brain KAT activity and KYNA levels with commensurate behavioral and neuropathological changes and suggest that compensatory changes or ontogenic expression of another isoform may account for the normalization of KYNA levels in the adult mKat-2(−/−) brain.